Análisis jurídico del artículo 226 del código civil referente a la terminación de la unión de hecho - Villavicencio Apolo, Jordy Guillermo (2016)
The present research work entitled "ANALYSIS LEGAL OF THE ARTICLE 226 OF THE CODE CIVIL REFERENCE TO THE TERMINATION OF THE UNION IN FACT" is relevant its study and analysis, since Ecuadorian legislation the constituent elements of the Union of fact are similar in other legislation, but did not agree with the grounds for its termination or dissolution. The Union of fact has its space within the provisions of the first book, title VI of the Civil Code, law that was amended in the year 2015, but despite this, they still exist gaps legal with respect to the issue that concerns us, causing serious damage and harm to couples who have decided to unite their lives through the legal figure of Union of fact; Since then to have lived some time, one of the two people voluntarily decide to put an end to this relationship, leaves his partner and children under age in the total helplessness, causing economic, psychological, and social; and, without the right to the abandoned partner can claim you bin them acquired by its partner during the time it lasted their relationship; Therefore this problem should be considered in several legal analyses and thus to consider alternative solutions that permit to guarantee real and effective way the legal security that we enjoy all Ecuadorians and Ecuadorian. The methodology is qualitative-quantitative which integrates methods, techniques and instruments for the problem statement, goals and determining instruments for the collection of information; which was tabbed, processed, substantiated by the literary context, materials and methods and results; obtaining conclusions and recommendations logical surveys and interviews made to professionals of the law and judges of the Judicial function. The proposal will allow through a procedure of course, provide greater guarantees to couples who decide to live in the form of Union of fact, through clear rules and you accurate regarding the completion of this form of family organization.